A Wave of Indo-Pacific Strategies and Canada’s Positioning: Reckoning with Global Power Rebalancing and the Crisis of Hyperglobalization - Massot, Pascale; Tiberghien, Yves (Revue Interventions économiques / Papers in Political Economy, 2024)
The Indo-Pacific concept grew out of a movement to refocus and redefine the Asia-Pacific region to include the Indian Ocean and South Asia, largely as a result of China’s rise. Over the past 10 years, an increasing number of Indo-Pacific strategies have been officially released in the region and beyond. The first question this article tackles is the following: What are the key drivers behind the rise of Indo-Pacific strategies? We argue that Indo-Pacific strategies have become a fast-moving experimenting space for countries searching for adjustment strategies to at least two concurrent deep trends in a changing global order: the great recent shift in the balance of power most vividly characterized by an increasingly assertive China, and the peaking of the liberal globalization experiment and the return of economic security to the fore. We are also concerned with the comparative angle to this question. In particular, how do Indo-Pacific strategies vary among key countries? And finally, how does the Canadian strategy fit within the broader landscape of Indo-Pacific strategies? In answer to these questions, the article develops a typology of existing Indo-Pacific strategies and how they each insert themselves in the current transitionary stage. Finally, we turn to Canada’s own Indo-Pacific strategy and its key features and drivers, including a discussion of Canada’s approach vis-à-vis China. We argue that this represents a touchstone in how Canada is responding to great power shifts and the erosion of the liberal international order.